The rural risk of digital exclusion: A case study of municipal digital health and social care services in Denmark - Barbara Fersch; Egon Bjørnshave Noe; Annette Aagaard Thuesen; Beate Langer (SSM: Qualitative Research in Health)
Digital solutions have the potential to contribute to a stronger inclusion of the rural population in health and welfare services in times of a more scattered infrastructure. However, in Denmark where there is a strong push towards a digitalization of these services, the demographic profile of the rural population, being older and with lower levels of education, implies that a large part of the population in digitally vulnerable positions resides here. In this article, we therefore focus on the risk of digital exclusion in rural areas. Drawing on interviews with frontline professionals involved in the provision of (partly) digitalized services and a volunteer, and on insights from a stakeholder workshop, we provide an investigation of both the mechanisms of digital exclusion and of how these are (at least partly) mitigated in the context of the provision of digital services by health and social care units of two Danish rural municipalities. Drawing on the concept of digital capital, we identify several preconditions and contextual aspects, such as cognitive impairment, that in combination with missing digital capital leads to digital exclusion, and we show how social capital such as family and acquaintances mitigates digital exclusion and the lack of a high enough level of digital capital in various ways. We demonstrate the analytical potential of digital capital and the capital perspective, as it both can open-up practice-oriented insights as well as clarify how the individual's opportunities for acquiring or compensating missing digital capital are related to societal inequalities.